Pengaruh Variasi Fraksi Volume Filler Terhadap Sifat Mekanik pada Komposit Polyester Berpenguat Serat Pelepah Pisang - Erlina Rosmawati; Syarifatunnisa Eka Apsarini; Utiya Hikmah; Nurun Nayiroh (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
The purpose of this study is to ascertain how changes in the volume proportion of banana stems affect the composite's mechanical characteristics and microscopic structure.  Banana stem fibre served as a natural reinforcement in this investigation together with a polyester matrix.  The selection of banana stem fibre was based on its broad availability and possible mechanism.  The hands lay-up approach is used in this study.  The volume proportion of banana stem fibre was varied from 0% to 25% in order to mould each sample into a composite.  A two-hour alkalisation treatment with 5% NaOH was applied to banana stem fibre. A Universal Testing Machine (UTM) was used to assess the samples' tensile strength, and an optical microscope was used to examine their microstructure.  According to the study's findings, the tensile strength values of composites with volume fractions of 0%, 10%, 15%, 20%, and 25% were 5.9 Mpa, 11.9 Mpa, 8.9 Mpa, and 7.9 Mpa, respectively.  It is evident that the sample with the best tensile stress value, 11.9 Mpa, has a 15% banana stem volume fraction.